Early detection of virus infections in potato by aphids and infrared remote sensing - Mayer, Maximilian (SLU/Dept. of Crop Production Ecology, 2016)
Potato is one of the most important crops worldwide. In recent years, breeding and advances in crop protection have made it possible to increase potato yield and production despite decreasing area harvested. Nonetheless problems with pests are still prevalent and can destroy big parts of the annual harvest. One of the mayor problems in potatoes are viruses, due to the lack of chemical control. The Potato Leaf Rolle Virus (PLRV) and the Potato Virus Y (PVY) are the most threatening viral diseases. Both are transmitted with aphids. While it has been shown, that the persistent virus PLRV attracts aphids through altered volatiles in potatoes, this proof was lacking for the non- persistent virus PVY. Our results of aphid olfactory response have shown that the odors of potato cultivars expressing a great amount of symptoms when infected with PVY attracted significantly more aphids than the odors from virus fee plants. However, only in early growing stages of the plants, PVY infected potatoes were more attractive for aphids. Viral diseases are also transferred in vegetative propagation with seed tubers. The plants derived from these infected tubers are the source for new virus infections in the field. Unfortunately, up to now, virus detection in plants is limited to serological (ELISA) and molecular (PCR) methods, which are destructive and time consuming. Early detection of PVY infected plants and their removal from the field is the most important measure to stop/reduce virus distribution by aphids. We demonstrated that mid- infrared imaging can be used to detect virus infections in early growing stages of plants before symptoms are visible to the human eye. The diagnosis of viral infections with infrared techniques became more accurate with the age of examined plants. Our studies indicate that remote sensing with mid infrared cameras can be used to identify PVY infected plants in a growing stage in which aphid attraction via odors occurs. Mid infrared sensing can therefore be used to detect infected plants before aphids arrive in the field.